2021
DOI: 10.1021/acs.jchemed.1c00637
|View full text |Cite
|
Sign up to set email alerts
|

Microscale Educational Kits for Learning Chemistry at Home

Abstract: Educational kits can improve the teaching of experimental sciences, providing an interesting strategy to be explored at home, especially during the COVID-19 pandemic. In this sense, chemistry kits based on a microscale design were developed encompassing safety, portability, efficacy, and low cost. They were successfully applied in regular classes and distance learning courses at the University of Saõ Paulo. This article provides the basic guidelines and is complemented with details and examples in the Supporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…In line with the previous research, the at-home-based laboratory experiment can improve lab work skills and students' learning motivation (Destino & Cunningham, 2020). The previous study also stated that one of the strategies to improve the students' skills and interest in science during a pandemic is the application of educational kits that can be explored at home (Toma, 2021). The spirit/motivation of students in science learning gives an impact on their interest in science so this will improve students' scientific attitude.…”
Section: Resultssupporting
confidence: 67%
“…In line with the previous research, the at-home-based laboratory experiment can improve lab work skills and students' learning motivation (Destino & Cunningham, 2020). The previous study also stated that one of the strategies to improve the students' skills and interest in science during a pandemic is the application of educational kits that can be explored at home (Toma, 2021). The spirit/motivation of students in science learning gives an impact on their interest in science so this will improve students' scientific attitude.…”
Section: Resultssupporting
confidence: 67%
“… 41 , 42 Furthermore, take-home chemistry kits for high school, two-year community college, and university students from Brazil and the United States address issues with student access to supplies and tools while offering a safe and often inexpensive alternative to traditional lab experiments. 43 45 Overall, there is a consistent motif of kitchen chemistry in terms of learning objectives, such as the realistic learning experiences akin to hands-on laboratories, active engagement with small-scale experiments, and problem-solving during the experiment rather than reading from a recipe. Nevertheless, kitchen chemistry does not fully mimic a laboratory setting and associated safety considerations for laboratories whose objectives are primarily derived from the acquisition of technical skills (e.g., upper-level synthesis techniques).…”
Section: Virtual Learning Paradigmmentioning
confidence: 99%
“…Kitchen chemistry has become increasingly accessible and has been proven to reinforce fundamental concepts (e.g., spectroscopy, standard purification techniques) (see Table , VL-1–6). For example, several authors from the United States and Spain have reported the use of cell phones to aid kitchen chemistry experiments, namely, colorimetric and fluorescence analyses in high school and college (an R1 institute) chemistry courses. , Furthermore, take-home chemistry kits for high school, two-year community college, and university students from Brazil and the United States address issues with student access to supplies and tools while offering a safe and often inexpensive alternative to traditional lab experiments. Overall, there is a consistent motif of kitchen chemistry in terms of learning objectives, such as the realistic learning experiences akin to hands-on laboratories, active engagement with small-scale experiments, and problem-solving during the experiment rather than reading from a recipe. Nevertheless, kitchen chemistry does not fully mimic a laboratory setting and associated safety considerations for laboratories whose objectives are primarily derived from the acquisition of technical skills (e.g., upper-level synthesis techniques).…”
Section: Virtual Learning Paradigmmentioning
confidence: 99%
“…Analytical Methods be further explored via spot tests, by reacting Au(III) ions and lithium ranelate in aqueous solution, and monitoring the nanoparticles with a smartphone colourimeter app. 21,22 The strategy provides not only a qualitative spot test assay specic to gold ions, but also the quantitative evaluation of gold ions with a smartphone, dispensing any sophisticated analytical equipment. As shown in Fig.…”
Section: Papermentioning
confidence: 99%